Manipulating polarization attenuation in NbS2–NiS2 nanoflowers through homogeneous heterophase interface engineering toward microwave absorption with shifted frequency bands - Yiru Fu; Yuping Wang; Junye Cheng; Yao Li; Jing Wang; Yongheng Jin; Deqing Zhang; Guangping Zheng; Maosheng Cao (Nano Materials Science)
Homogeneous heterogeneous (heterophase) interfaces regulated with low energy barriers have a fast response to applied electric fields and could provide a unique interfacial polarization, which facilitate the transport of electrons across the substrate. Such regulation on the interfaces is effective in modulating electromagnetic wave absorbing materials. Herein, we construct NbS2–NiS2 heterostructures with NiS2 nanoparticles uniformly grown in NbS2 hollow nanospheres, and such particular structure enhances the interfacial polarization. The strong electron transfer at the interface promotes electron transport throughout the material, which results in less scattering, promotes conduct ion loss and dielectric polarization relaxation, improves dielectric loss, and results in a good impedance matching of the material. Consequently, the absorbing band may be successful tuned. By regulating the amount of NiS2, the heterogeneous interface is finely alternated so that the overall wave-absorbing performance is shifted to lower frequencies. With a NiS2 content of 15 ​wt% and an absorber thickness of 1.84 ​mm, the minimum reflection loss at 14.56 ​GHz is −53.1 ​dB, and the effective absorption bandwidth is 5.04 ​GHz; more importantly, the minimum reflection loss in different bands is −20 dB, and the microwave energy absorption rate reaches 99% when the thickness is about 1.5–4.5 ​mm. This work demonstrates the construction of homogeneous heterostructures is effective in improving the electromagnetic absorption properties, providing guideline for the synthesis of highly efficient electromagnetic absorbing materials.